Trophic activity of pedofauna in two gardens of Saint-Petersburg (experience of using the express bait-lamina test methid) - A. A. Kuzmina; E. V. Pyatina; E. A. Zhukova; E. A. Gorbunova; E. Yu. Sukhacheva (Бюллетень Почвенного института им. В.В. Докучаева)
The plant and soil cover of cities functions as their ecological framework. Soil invertebrates play an important role in urban ecosystems. Trophic activity of pedofauna is an integral indicator of its condition. The trophic activity of macroand mesopedofauna in the soils of the gardens of the Russian Museum (St. Petersburg) was determined by the express method baitlamina test. The average values of the degree of consumption of bait by pedobionts amounted to 10.9 ± 1.6% for the Summer Garden and 8.5 ± 3.5% for the Mikhailovsky Garden. The variability of trophic activity indices between different sample areas was established – in the Summer Garden it varies from 2 ± 6.2% to 21.8 ± 8.4%, and in the Mikhailovsky Garden – from 2.8 ± 4.5% to 19.3 ± 8.8%. Differences in trophic activity within the vegetation season were noted. The lowest degree of bait consumption (less than 2%) was observed in the driest and hottest months in the middle of the vegetation period, and the highest (within 19–22%) – at the beginning and end of the vegetation period under the most favorable hydrothermal conditions.